2006
DOI: 10.1017/s026646740600352x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial associations of humus, nutrients and soils in mixed dipterocarp forest at Lambir, Sarawak, Malaysian Borneo

Abstract: Discrete humus layers are common on podzols under temperate coniferous and tropical heath forests, and patchy layers also occur under some temperate broadleaved forests on non-podzolic soils. We used multiple data sets to test the reported association of humus with oligotrophic but non-podzolic soils under non-heath dipterocarp forest at Lambir, Sarawak. We examined the distribution, morphology and nutrient dynamics of necromass on soils derived from sandstone and shale. Concentrations of the main mineral nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 51 publications
(64 reference statements)
2
78
0
2
Order By: Relevance
“…Sandstone-derived soils are humult utisols or sandy haplic acrisols with substantial surficial raw humus and root mat and relatively low nutrient and water retention. Shale-derived soils are clay-rich ultisols generally lacking a humus layer and root mat and have greater nutrient and moisture retention (Baillie et al 2006). Four soil types have been described based on differences in soil chemistry (C, N and P and exchangeable K, Ca and Mg) and elevation (Davies et al 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sandstone-derived soils are humult utisols or sandy haplic acrisols with substantial surficial raw humus and root mat and relatively low nutrient and water retention. Shale-derived soils are clay-rich ultisols generally lacking a humus layer and root mat and have greater nutrient and moisture retention (Baillie et al 2006). Four soil types have been described based on differences in soil chemistry (C, N and P and exchangeable K, Ca and Mg) and elevation (Davies et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Davies et al (2005) found that of the abundant species at Lambir, 73 % had distributions significantly aggregated on at least one of the four soil types. Here we focus on two soil types, clay and sandy loam, at the extremes of this gradient that differ most in soil properties (Baillie et al 2006). Supply rates of NH þ 4 and NO À 3 in surface soil (top 10 cm) of clay and sandy loam were quantified in the 52-ha plot over a 5-week period using anion and cation exchange resins as part of a separate study (Kochsiek et al 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1991, a 52-ha plot (hereafter, Lambir) was established in the Park following standardized methods (Condit 1998) and pegged with permanent markers at every 20-m grid corner (Figure 1). Floristic composition, stand structure, soils, soil nutrient and water contents, and geomorphology of Lambir are described elsewhere (Baillie et al 2006, Lee et al 2002, Russo et al 2010, Tan et al 2009). …”
Section: Study Sitementioning
confidence: 99%
“…We tested the hypothesis that regimes of PAR differ significantly in the understorey of rain forest growing on four soil types along an edaphic gradient in Borneo. Soils along this gradient range from coarse loams that are sandstonederived, nutrient-depleted and well-drained, to clays that are shale-derived, less nutrient-depleted and less welldrained (Baillie et al 2006, Russo et al 2010, Tan et al 2009), but the forests share the same rainfall regime, as they are located at one site. Variation in light regimes between and within forest types was characterized in terms of total daily PPFD and the frequency, duration and intensity of sunflecks and in terms of their seasonal variation between the non-monsoon season and the generally cloudier, early monsoon season.…”
Section: Introductionmentioning
confidence: 99%